TINJAUAN PADA CV BINA PERKASA ATAS SISTEM: PENJUALAN KREDIT DAN PENGENDALIAN INTERN - Dewi Dwijayanti Lamsinar Purba; Rutman Lumbantoruan SE., MM (Fakultas Ekonomi Universitas Kristen Indonesia, 2018)
Credit sales are transactions between the company and the buyer of goods or services which means there is the emergence of a receivable. CV. Bina Perkasa impose two kinds of systems sales ie sales in cash and credit sales. Most sales take place in the CV. Bina Perkasa is credit sales. This study aims to determine the credit sales system procedures and internal control at CV. Bina Perkasa. In carrying out this study, the authors do the Job Training (PKL) for one month in the company. procedure that goes with that in the procedure CV. Bina Perkasa is in conformity with the general credit sales procedures such as the procedure of sale, warehouse procedures, delivery procedures, procedures of credit and accounts receivable procedures. Implementation of internal control that goes with that in internal control in CV. Bina Perkasa also is in conformity with the internal control system of credit sales are common as the authorization of transactions, assets and records security, segregation of duties and adequate documents and records.